Carbohydrate fear, skinfold targets and body image issues: a qualitative analysis of player and stakeholder perceptions of the nutrition culture within elite female soccer. Issue 5 (1st December 2022) - McHaffie, Samuel J.; Langan-Evans, Carl; Morehen, James C.; Strauss, Juliette A.; Areta, José L.; Rosimus, Christopher; Evans, Martin; Elliott-Sale, Kirsty J.; Cronin, Colum J.; Morton, James P.
ABSTRACT: Purpose: This qualitative study explores player and stakeholder perceptions of the role of nutrition in supporting player development and performance in elite female soccer. Methods: Semi-structured interviews (36 ± 18 mins in length) were conducted with 47 participants, including players (n = 12), parents (n = 9), coaches (n = 9), sport scientists (n = 7), nutritionists (n = 5) and medical staff (n = 5). Via thematic analysis, data provided an insight into the nutrition culture within elite women's soccer. Results and conclusions: Data demonstrate that considerable confusion and misconceptions exist amongst players and stakeholders regarding the theoretical underpinning and practical application of meeting energy requirements. As such, it is perceived that players 'under-fuel', which is likely caused by misunderstandings about the impact of carbohydrate intake on body composition, a fear of weight gain and the associated impacts upon body image. The 'carbohydrate fear' that is experienced by players is exacerbated by external pressures arising from social media, key stakeholders (e.g., coaches) and the skinfold culture surrounding measurement of body composition. Such cultural issues are amplified by the lack of full-time professionally accredited nutritionists overseeing the provision of nutrition support. Indeed, the infrastructure supporting the women's game (e.g. staffing resource, on-site food provision, player education programmes, etc.) was considered incomparable to the men's game. When taken together, our data provide a platform for which to develop organisational, stakeholder and player centred education and behaviour change interventions that strive to promote a positive performance nutrition culture within the women's game.